Covertaction Information Bulletin - CovertAction Publications (My University, 1980)
Article about CIA and the Madia
Covertaction quarterly
35 pgs. Typescript, letter-sized, sepia-toned, in fairly good condition
Keywords: United States Central Intelligence Agency - Periodicals; Intelligence service - United States - Periodicals; Intelligence service